Farmer and Veterinarian Attitudes towards the Bovine Tuberculosis Eradication Programme in Spain: What Is Going on in the Field? - Ciaravino, Giovanna; Ibarra, Patricia; Casal, Ester; Lopez, Sergi; Espluga, Josep; Casal, Jordi; Napp, Sebastian; Allepuz, Alberto (Frontiers in Veterinary Science, 2017)
The effectiveness of health interventions against bovine tuberculosis (bTB) is influenced by several “non-biological” factors that may hamper bTB detection and control. Although the engagement of stakeholders is a key factor for the eradication programme's success, social factors have been often ignored in the control programmes of animal diseases, especially in developed countries. In this study, we used a qualitative approach to investigate perceptions, opinions, attitudes and beliefs of farmers and veterinarians that may influence the effectiveness of the Spanish bTB eradication programme. The study was carried out in two phases. Firstly, 13 key representatives of different groups involved in the programme were interviewed through exploratory interviews to identify most relevant themes circulating in the population. Interviews focused on strong and weak points of the programme; reasons for failure to achieve eradication; benefits of being disease free; future perspectives and proposed changes to the programme. Based on these results, a thematic guide was developed and detailed information was gained through face-to-face in-depth interviews conducted on a purposive sample of 39 farmers and veterinarians. Data was analysed following an ethnographic methodology. Main results suggested that the bTB programme is perceived as a law enforcement duty without an adequate motivation of some stakeholders and a general feeling of distrust arose. The complexity of bTB epidemiology combined with gaps in knowledge and weak communication throughout stakeholders contributed to causing disbelief, which in turn generated different kinds of guesses and interpretations. Low reliability in the routine skin test for bTB screening was expressed and the level of confidence on test results interpretation was linked with skills and experience of public and private vets in the field. Lack of training for farmers and pressure faced by veterinarians during field activities also emerged. Few benefits of being bTB free were perceived and comparative grievances referred to wildlife and other domestic reservoirs, sector-specific legislation for bullfighting farms and the absence of specific health legislation for game hunting farms were reported. Understanding reasons for demotivation and scepticism may help institutions to ensure stakeholders’ collaboration and increase the acceptability of control measures leading to an earlier achievement of eradication.